Pengaruh Motivasi Dan Akreditasi Terhadap Keputusan Memilih Program Studi Agribisnis Dengan Konformitas Sebagai Varibel Mediasi Pada Politeknik Pertanian Negeri Payakumbuh - Dewi Maya Sari; Edi Ariyanto (STIE AMKOP, 2023)
This research aimed to understand how motivation, accreditation, and conformity influence the decision to choose the Agribusiness program at Politeknik Pertanian Negeri Payakumbuh. The study included 97 students from semester II and IV, and a random sample of 95 students was used for data collection. The data were collected through questionnaires using a Likert scale and analyzed using Structural Equation Modeling (SEM) with smartPLS software. The results showed that motivation had a positive and significant effect on the decision to choose the Agribusiness program (regression coefficient: 0.605, p-value: 0.000). Similarly, accreditation and conformity also had a positive and significant impact on the decision (accreditation: regression coefficient: 0.173, p-value: 0.040; conformity: regression coefficient: 0.162, p-value: 0.031). Furthermore, conformity was tested as a mediating variable between motivation and accreditation's influence on the decision. The results showed that conformity had a positive effect but was not statistically significant (regression coefficient for motivation: 0.009, p-value: 0.720; regression coefficient for accreditation: 0.074, p-value: 0.072). In conclusion, motivation, accreditation, and conformity all play a role in influencing students' decisions to choose the Agribusiness program at Politeknik Pertanian Negeri Payakumbuh. However, conformity's role as a mediator was not significant in this study. Keywords: Motivation, Accreditation, Conformity, Decision to choose